ANALISA PENGARUH GAJI, LINGKUNGAN KERJA, PELATIHAN DAN PENGEMBANGAN TERHADAP KEPUASAN KARYAWAN PADA TONYS VILLAS & RESORT, SEMINYAK-BALI - I Made Angga Adiguna; Yunus Handoko; Moh Maskan (KRISNA: Kumpulan Riset Akuntansi, 2024)
Abstract The progress and sustainability of the organization is largely determined by the Human Resources element. Because Human Resources is the core of an organization. The purpose of this study was to find out whether 1) Salary has a partial effect on Employee Satisfaction, 2) Work Environment has a partial effect on Employee Satisfaction, 3) Training and development has a partial effect on Employee Satisfaction and 4) Does Salary, Work Environment, Training and development have a simultaneous effect on employee satisfaction at Tonys Villas & Resort, Seminyak-Bali This study uses a quantitative descriptive approach to the employees of Tonys Villas & Resort, Seminyak-Bali. The research population was Tonys Villas & Resort Seminyak-Bali contract employees with a sample of 80 respondents using the census method or saturated sample. The inferential statistical analysis technique uses multiple linear regression analysis with the help of SPSS.25.0 software. The test instruments used were validity and reliability tests using a bivariate correlation approach, analysis of the correlation of indicators to constructs using conformational factor analysis and hypothesis testing. The results of the study show that salary, work environment and training and development have an effect simultaneously on employee job satisfaction, then it is partially found that salary and training and development have an effect on employee satisfaction but the work environment has no effect on employee job satisfaction at Tonys Villas & Resort, Seminyak – Bali. Keywords: Salary, Work Environment, Training and Development, Employee Satisfaction